Method for manufacturing porous composite material containing silica aerogel

KR1020260122191APending Publication Date: 2026-08-11KOREA INST OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
KR1020250013845
Authority / Receiving Office
KR · KR
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-02-04
Publication Date
2026-08-11

Smart Images

  • Figure PAT00008_ABST
    Figure PAT00008_ABST
Patent Text Reader

Abstract

The present disclosure relates to a method for manufacturing a porous composite material comprising silica aerogel. Specifically, the method comprises the steps of: applying a polymer solution comprising silica aerogel and a polymer resin to a substrate; and immersing the substrate coated with the polymer solution in a non-solvent solution to perform a phase inversion and form a porous composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present disclosure relates to a method for manufacturing a porous composite material comprising silica aerogel.

[0002] [Explanation of government-supported R&D]

[0003] This research was conducted under the supervision of the Korea Institute of Science and Technology and supported by the Ministry of SMEs and Startups’ Tech-Bridge Commercialization Technology Development Project (Development of flame-retardant / flexible / insulating polymer composite materials based on silica aerogel, Project No.: 2420000560), the National Research Council of Science and Technology’s Research Operation Support Project (Development of lightweight platform technology for recyclable future air mobility structural materials and components, Project No.: 2710024158), and the Ministry of Science and ICT’s Creative Convergence Research Project (Development of technology for fabricating high-impregnation prepreg based on surface-modified lignin carbon fiber). Background Technology

[0004] Aerogels possess a nanoporous structure with a porosity of over 90% and a specific surface area of ​​several hundred to 1,000 m² 2 It is a transparent or translucent ultra-low density advanced material with a density of approximately 1 / g. As such, aerogels are applied in various fields as ultrafine, porous, low-density materials, such as catalyst supports, thermal insulation, noise shielding, and particle accelerators.

[0005] In particular, silica aerogel is a highly efficient super-insulating material that can be used in refrigerators, freezers, and heat storage devices due to its high light transmittance and extremely low thermal conductivity. However, silica aerogel, which is generally manufactured in powder or bead form, exhibits very weak strength due to its high brittleness, easily breaking even under minor impacts. Furthermore, because it is difficult to process into various thicknesses and shapes, its application as an insulating material is currently very challenging despite its excellent thermal insulation properties.

[0006] Aerogels are primarily manufactured through a supercritical drying process, but since the supercritical process is carried out at high temperature and pressure, it contributes to increased manufacturing costs. Furthermore, aerogels manufactured through the supercritical process are 99% filled with air in the form of a framework. When mixing the aerogel with other reactants, solvents or solutes penetrate into the interior of the aerogel, increasing the viscosity of the compound and making mixing impossible. Consequently, it is difficult to composite or mix with other materials, and there is a problem in that the porous aerogel cannot exhibit its characteristics.

[0007] To address these issues, technologies are being attempted to manufacture aerogels in the form of blanket-type aerogels or expanding packs by filling nonwoven fabrics with aerogel; however, aerogels manufactured in this way have the problem of degrading the properties of the aerogel itself. Prior art literature

[0008] Republic of Korea Published Patent Application No. 10-2017-0072790 The problem to be solved

[0009] The present disclosure aims to provide a composite material that overcomes the existing disadvantages of silica aerogel, which is difficult to maintain its shape when used alone, and maximizes lightness and thermal insulation. means of solving the problem

[0010] To achieve the above objective, one embodiment of the present invention comprises the step of applying a polymer solution comprising silica aerogel and a polymer resin to a substrate; and

[0011] A method for manufacturing a porous composite material comprising silica aerogel is provided, comprising the step of forming a porous composite material by immersing a substrate coated with the above polymer solution in a non-solvent solution to perform a phase inversion.

[0012] Another embodiment of the present invention provides a porous composite material manufactured by the above method.

[0013] Another embodiment of the present invention provides an insulating material comprising a porous composite material manufactured by the above method. Effects of the invention

[0014] The composite material according to the present disclosure efficiently maintains the shape of silica aerogel, which is difficult to maintain when used alone, and can have excellent lightweight and thermal insulation properties. Brief explanation of the drawing

[0015] Figures 1a to 1d show the results of verifying flexibility according to Test Example 1. Figures 2a and 2b show the results of confirming the pore structure using a scanning electron microscope (SEM) according to Test Example 2. Figure 3 shows the thermogravimetric analysis (TGA) results according to Test Example 3. Figure 4 shows the results of measuring the heat release rate (HRR) according to Test Example 4. Figures 5a to 5d show the results of visually confirming the flame-retardant properties according to Test Example 5. Figures 6a to 6d show the results of confirming the flame retardant properties according to Test Example 5 through SEM images. Specific details for implementing the invention

[0016] The present invention will be described in detail below.

[0017] In one aspect, the present invention may relate to a method for manufacturing a porous composite material comprising silica aerogel.

[0018] In one embodiment, the method may include the step of applying a polymer solution comprising silica aerogel and a polymer resin to a substrate; and the step of immersing the substrate coated with the polymer solution in a non-solvent solution to perform a phase inversion to form a porous composite material.

[0019] In one embodiment, the polymer resin may be at least one selected from the group consisting of polyetherimide (PEI), polyimide (PI), polyamideimide (PAI), polystyrene (PS), polyetheretherketone (PEEK), polycarbonate (PC), polyethylene terephthalate (PET), polyethylene (PE), polypropylene (PP), acrylonitrile butadiene styrene (ABS), polybenzimidazole (PBI), polyvinyl chloride (PVC), polysulfone (PSU), polyphenylene sulfide (PPS), polyurethane (PU), ethylene-vinyl acetate (EVA), polylactic acid (PLA), polyoxymethylene (POM), and polytetrafluoroethylene (PTFE), which are thermoplastic polymers based on condensation polymerization and radical polymerization, but is not limited thereto, and any related polymer resin that can be manufactured by copolymerization is possible.

[0020] In one embodiment, the polymer solution may be obtained by dissolving and mixing the silica aerogel and the polymer resin in an organic solvent.

[0021] In one embodiment, the silica aerogel may be added to the organic solvent in an amount of 1 to 99 weight percent relative to the total weight of the silica aerogel and the polymer resin.

[0022] Specifically, the silica aerogel may be added to the organic solvent in an amount of 1 wt% or more, 5 wt% or more, 10 wt% or more, 15 wt% or more, 20 wt% or more, 25 wt% or more, 30 wt% or more, 35 wt% or more, 40 wt% or more, 45 wt% or more, 50 wt% or more, 55 wt% or more, 60 wt% or more, 70 wt% or more, 80 wt% or more, or 90 wt% or more, relative to the total weight of the silica aerogel and the polymer resin; additionally, the silica aerogel may be added in an amount of 99 wt% or less, 90 wt% or less, 80 wt% or less, 75 wt% or less, 70 wt% or less, 65 wt% or less, 60 wt% or less, 55 wt% or less, 50 wt% or less, 45 wt% or less, 40 wt% or less, 35 wt% or less, relative to the total weight of the silica aerogel and the polymer resin. It can be added to the organic solvent in an amount of 30 weight% or less, 20 weight% or less, or 10 weight% or less.

[0023] In one embodiment, the polymer resin and the silica aerogel may be dissolved in the organic solvent in a weight ratio of 1:99 to 99:1 (polymer resin: silica aerogel).

[0024] Specifically, the weight ratio of the polymer resin and the silica aerogel (polymer resin : silica aerogel) is 1 : 99 or more, 1 : 90 or more, 1 : 80 or more, 1 : 70 or more, 1 : 60 or more, 1 : 50 or more, 1 : 40 or more, 1 : 30 or more, 1 : 20 or more, 1 : 10 or more, 1 : 5 or more, 1 : 1 or more, 1.5 : 1 or more, 2 : 1 or more, 7 : 3 or more, 2.5 : 1 or more, 3 : 1 or more, 3.5 : 1 or more, 4 : 1 or more, 4.5 : 1 or more, 5 : 1 or more, 5.5 : 1 or more, 6 : 1 or more, 6.5 : 1 or more, 7 : 1 or more, 7.5 : 1 or more, 8 : 1 or more, 8.5 : 1 The ratio may be 99:1 or more, 10:1 or more, 20:1 or more, 30:1 or more, 40:1 or more, 50:1 or more, 60:1 or more, 70:1 or more, 80:1 or more, or 90:1 or more, and additionally, the weight ratio of the polymer resin and the silica aerogel (polymer resin : silica aerogel) may be 99:1 or less, 90:1 or less, 80:1 or less, 70:1 or less, 60:1 or less, 50:1 or less, 40:1 or less, 30:1 or less, 20:1 or less, 10:1 or less, 9:1 or less, 8.5:1 or less, 8:1 or less, 7.5:1 or less, 7:1 or less, 6.5:1 or less, 6:1 or less, or 5.5:1. It may be 5:1 or less, 4.5:1 or less, 4:1 or less, 3.5:1 or less, 3:1 or less, 2.5:1 or less, 7:3 or less, 2:1 or less, 1.5:1 or less, 1:1 or less, 1:10 or less, 1:20 or less, 1:30 or less, 1:40 or less, 1:50 or less, 1:60 or less, 1:70 or less, or 1:80 or less.

[0025] In one embodiment, the silica aerogel and the polymer resin can be dissolved in the organic solvent at a temperature of 60 to 80°C and for 20 to 30 hours.

[0026] Specifically, the silica aerogel and the polymer resin may be dissolved in the organic solvent at a temperature of 60°C or higher, 61°C or higher, 62°C or higher, 63°C or higher, 64°C or higher, 65°C or higher, 66°C or higher, 67°C or higher, 68°C or higher, 69°C or higher, 70°C or higher, 71°C or higher, 72°C or higher, 73°C or higher, 74°C or higher, 75°C or higher, 76°C or higher, 77°C or higher, 78°C or higher, or 79°C or higher, and additionally, at a temperature of 80°C or lower, 79°C or lower, 78°C or lower, 77°C or lower, 76°C or lower, 75°C or lower, 74°C or lower, 73°C or lower, 72°C or lower, 71°C or lower, 70°C or lower, 69°C or lower, 68°C or lower, 67°C or lower, 66°C or lower, 65°C or lower, 64°C or lower, It can be dissolved in the organic solvent at a temperature of 63℃ or lower or 62℃ or lower.

[0027] More specifically, the silica aerogel and the polymer resin may be dissolved in the organic solvent for 20 hours or more, 21 hours or more, 22 hours or more, 23 hours or more, 24 hours or more, 25 hours or more, 26 hours or more, 27 hours or more, 28 hours or more, or 29 hours or more, and may also be dissolved in the organic solvent for 30 hours or less, 29 hours or less, 28 hours or less, 27 hours or less, 26 hours or less, 25 hours or less, 24 hours or less, 23 hours or less, 22 hours or less, or 21 hours or less.

[0028] In one embodiment, the organic solvent may be at least one selected from a polar aprotic solvent, a polar protic solvent, a nonpolar solvent, and a halogenated organic solvent.

[0029] In one embodiment, depending on the compatibility of the solvent, a solvent with very high compatibility that can dissolve the polymer is called a good solvent, a solvent that has compatibility but is not sufficient to dissolve it is called a poor solvent, and a solvent with no compatibility at all is called a non-solvent. Depending on the compatibility between the polymer and the solvent, a good solvent and a non-solvent can be selected, and in the case of a good solvent and a non-solvent, the following solvents can be used alone or in combination.

[0030] In one embodiment, the organic solvent may be at least one selected from the group consisting of N-methyl-2-pyrrolidone (NMP), dimethylacetamide (DMAc), dimethylformamide (DMF), methylene chloride (MC), and dimethyl sulfoxide (DMSO), tetrahydrofuran (THF), acetone, 1,4-dioxane, chloroform, ethylene glycol, propylene carbonate, trichloroethylene (TCE), and methyl ethyl ketone (MEK).

[0031] In one embodiment, the substrate may be selected from a metal substrate, a glass substrate, a silicon substrate, and a plastic substrate.

[0032] In one embodiment, the polymer solution may be applied to the substrate by any one method selected from doctor's knife, spin coating, dip coating, roll coating, screen coating, spray coating, flow coating, screen printing, ink jet, and drop casting.

[0033] In one embodiment, the average particle size (D50) of the silica aerogel may be 0.1 to 1,000 μm.

[0034] Specifically, the average particle size (D50) of the silica aerogel may be 0.1 μm or more, 0.2 μm or more, 0.3 μm or more, 0.4 μm or more, 0.5 μm or more, 0.6 μm or more, 0.7 μm or more, 0.8 μm or more, 0.9 μm or more, 1 μm or more, 2 μm or more, 3 μm or more, 4 μm or more, 5 μm or more, 6 μm or more, 7 μm or more, 8 μm or more, 9 μm or more, 10 μm or more, 20 μm or more, 30 μm or more, 40 μm or more, 50 μm or more, 60 μm or more, 70 μm or more, 80 μm or more, 90 μm or more, 100 μm or more, or 500 μm or more, and additionally, the average particle size (D50) of the silica aerogel It may be 1,000 μm or less, 950 μm or less, 900 μm or less, 850 μm or less, 800 μm or less, 750 μm or less, 700 μm or less, 650 μm or less, 600 μm or less, 550 μm or less, 500 μm or less, 450 μm or less, 400 μm or less, 350 μm or less, 300 μm or less, 250 μm or less, 200 μm or less, 150 μm or less, 100 μm or less, 90 μm or less, 80 μm or less, 70 μm or less, 60 μm or less, 50 μm or less, 40 μm or less, 30 μm or less, 20 μm or less, or 10 μm or less.

[0035] In one embodiment, the nonsolvent may be selected from the group consisting of water, C1-C6 lower alcohols, alkane solvents, and mixtures thereof.

[0036] In one embodiment, the method may further include, after the step of forming the porous composite material, the step of immersing the substrate on which the porous composite material is formed in distilled water to remove residual solvent and drying it.

[0037] In one embodiment, the drying may be performed at a temperature of 80 to 120°C. Specifically, the drying may be performed at a temperature of 80°C or higher, 85°C or higher, 90°C or higher, 95°C or higher, 100°C or higher, 105°C or higher, 110°C or higher, or 115°C or higher, and may also be performed at a temperature of 120°C or lower, 115°C or lower, 110°C or lower, 105°C or lower, 100°C or lower, 95°C or lower, 90°C or lower, or 85°C or lower.

[0039] In another aspect, the present invention may relate to a porous composite material manufactured by the above method.

[0040] In one embodiment, the porous composite material may be in the form of a film or a foam.

[0041] In one embodiment, the thickness of the film or foam may be 1 μm to 30 cm.

[0042] Specifically, the thickness of the film or foam may be 1 μm or more, 10 μm or more, 20 μm or more, 30 μm or more, 40 μm or more, 50 μm or more, 60 μm or more, 70 μm or more, 80 μm or more, 90 μm or more, 100 μm or more, 500 μm or more, 1 mm or more, 2 mm or more, 3 mm or more, 4 mm or more, 5 mm or more, 6 mm or more, 7 mm or more, 8 mm or more, 9 mm or more, 1 cm or more, 2 cm or more, 3 cm or more, 4 cm or more, 5 cm or more, 6 cm or more, 7 cm or more, 8 cm or more, 9 cm or more, 10 cm or more, 15 cm or more, 20 cm or more, or 25 cm or more, and additionally, the thickness of the film or foam may be 30 cm or less, 25 cm or less, 20 cm or less, 15 cm or less, It may be 10 cm or less, 9 cm or less, 8 cm or less, 7 cm or less, 6 cm or less, 5 cm or less, 4 cm or less, 3 cm or less, 2 cm or less, 1 cm or less, 9 mm or less, 8 mm or less, 7 mm or less, 6 mm or less, 5 mm or less, 4 mm or less, 3 mm or less, 2 mm or less, 1 mm or less, 800 μm or less, 500 μm or less, 200 μm or less, 100 μm or less, 90 μm or less, 80 μm or less, 70 μm or less, 60 μm or less, 50 μm or less, 40 μm or less, 30 μm or less, 20 μm or less, or 10 μm or less.

[0043] In one embodiment, the porous composite material may be used in a temperature range of -200°C to 400°C.

[0044] Specifically, the porous composite material may be used at a temperature of -200°C or higher, -150°C or higher, -100°C or higher, -50°C or higher, 0°C or higher, 50°C or higher, 100°C or higher, 150°C or higher, 200°C or higher, 250°C or higher, 300°C or higher, or 350°C or higher. Additionally, the porous composite material may be used at a temperature of 400°C or lower, 350°C or lower, 300°C or lower, 250°C or lower, 200°C or lower, 150°C or lower, 100°C or lower, 50°C or lower, 0°C or lower, -50°C or lower, -100°C or lower, or -150°C or lower.

[0045] In one embodiment, the thermal conductivity of the porous composite material may be 0.02 to 0.052 W / mK. Specifically, the thermal conductivity of the porous composite material may be 0.02 W / mK or higher, 0.03 W / mK or higher, or 0.04 W / mK or higher, and may also be 0.0518 W / mK or lower, 0.05 W / mK or lower, 0.048 W / mK or lower, 0.0472 W / mK or lower, 0.047 W / mK or lower, or 0.0465 W / mK or lower.

[0046] In one embodiment, the average density of the porous composite material is 0.1 to 0.34 g / cm³ 3 It may be. Specifically, the average density of the porous composite material is 0.1 g / cm³. 3 Above, 0.2 g / cm³ 3 Above, 0.21 g / cm³ 3 Above, 0.22 g / cm³ 3 Above, 0.23 g / cm³ 3 Above, 0.24 g / cm³ 3 Above, 0.25 g / cm³ 3 Above, 0.26 g / cm³ 3 Above, 0.27 g / cm³ 3 Above, 0.28 g / cm³ 3 Above, 0.29 g / cm³ 3 Above, 0.3 g / cm³ 3 Above, 0.31 g / cm³ 3Above, 0.32 g / cm³ 3 Above or 0.33 g / cm³ 3 It may be more than, and also, 0.34 g / cm³ 3 Below, 0.33 g / cm³ 3 Below, 0.32 g / cm³ 3 Below, 0.31 g / cm³ 3 Below, 0.3 g / cm³ 3 Below, 0.29 g / cm³ 3 Below, 0.28 g / cm³ 3 Below, 0.27 g / cm³ 3 Below, 0.26 g / cm³ 3 Below, 0.25 g / cm³ 3 Below, 0.24 g / cm³ 3 Below, 0.23 g / cm³ 3 Below, 0.22 g / cm³ 3 Less than or equal to 0.21 g / cm³ 3 It may be less than.

[0048] In another aspect, the present invention may relate to an insulating material comprising a porous composite material manufactured by the above method.

[0050] As one embodiment, the present invention may provide the following embodiments.

[0051] A first embodiment comprises the step of applying a polymer solution containing silica aerogel and a polymer resin to a substrate; and

[0052] A method for manufacturing a porous composite material comprising silica aerogel can be provided, comprising the step of forming a porous composite material by immersing a substrate coated with the above polymer solution in a non-solvent solution to perform a phase inversion.

[0053] A second embodiment may provide a method in which, in the first embodiment, the polymer resin is at least one selected from the group consisting of polyetherimide (PEI), polyimide (PI), polyamideimide (PAI), polystyrene (PS), polyetheretherketone (PEEK), polycarbonate (PC), polyethylene terephthalate (PET), polyethylene (PE), polypropylene (PP), acrylonitrile butadiene styrene (ABS), polybenzimidazole (PBI), and polyvinyl chloride (PVC), polysulfone (PSU), polyphenylene sulfide (PPS), polyurethane (PU), ethylene-vinyl acetate (EVA), polylactic acid (PLA), polyoxymethylene (POM), and polytetrafluoroethylene (PTFE).

[0054] A third embodiment may provide a method in which, in one or more of the first and second embodiments, the polymer solution is obtained by dissolving and mixing the silica aerogel and the polymer resin in an organic solvent.

[0055] A fourth embodiment may provide a method in which, in one or more of the first to third embodiments, the organic solvent is at least one selected from a polar aprotic solvent, a polar protic solvent, a nonpolar solvent, and a halogenated organic solvent.

[0056] The fifth embodiment may provide a method in which, in one or more of the first to fourth embodiments, the organic solvent is at least one selected from the group consisting of N-methyl-2-pyrrolidone (NMP), dimethylacetamide (DMAc), dimethylformamide (DMF), methylene chloride (MC), dimethyl sulfoxide (DMSO), tetrahydrofuran (THF), acetone, 1,4-dioxane, chloroform, ethylene glycol, propylene carbonate, trichloroethylene (TCE), and methyl ethyl ketone (MEK).

[0057] The sixth embodiment may provide a method in which, in one or more of the first to fifth embodiments, the substrate is selected from a metal substrate, a glass substrate, a silicon substrate, and a plastic substrate.

[0058] The seventh embodiment may provide a method in which, in one or more of the first to sixth embodiments, the polymer solution is applied to the substrate by any one method selected from doctor's knife, spin coating, dip coating, roll coating, screen coating, spray coating, flow coating, screen printing, ink jet, and drop casting.

[0059] The eighth embodiment may provide a method in which, in one or more of the first to seventh embodiments, the nonsolvent is selected from the group consisting of water, C1-C6 lower alcohols, alkane solvents, and mixtures thereof.

[0060] The ninth embodiment can provide a method in which, in one or more of the first to eighth embodiments, the average particle size of the silica aerogel is 0.1 to 1,000 μm.

[0061] The 10th embodiment is, in one or more of the 1st to 9th embodiments, after the step of forming the porous composite material,

[0062] A method may be provided that further includes the step of immersing the substrate on which the above-mentioned porous composite material is formed in distilled water to remove residual solvent and drying it.

[0063] The 11th embodiment may provide a porous composite material manufactured by a method according to one or more of the 1st to 10th embodiments.

[0064] The 12th embodiment may provide a porous composite material in the form of a film or foam, as in the 11th embodiment.

[0065] The 13th embodiment may provide a porous composite material in which, in one or more of the 11th to 12th embodiments, the thickness of the film or foam is 1 μm to 30 cm.

[0066] The 14th embodiment can provide a porous composite material that is used in a temperature range of -200°C to 400°C in one or more of the 11th to 13th embodiments.

[0067] The 15th embodiment may provide an insulating material comprising a porous composite material manufactured by a method according to one or more of the 1st to 10th embodiments.

[0069] The contents of the present invention will be explained in more detail below through examples and test examples. However, these examples and test examples are provided merely to help understand the contents of the present invention, and the scope of the present invention is not limited to these examples and test examples. Modifications, substitutions, and insertions commonly known in the art may be performed, and such are also included within the scope of the present invention.

[0071] Example 1

[0072] Polyetherimide (PEI) (Ultem 1000, density 1.27 g / cm³ 3 A polymer solution was prepared by homogeneously dissolving 9 g of pellets and 1 g of silica aerogel (SI) (REM tech, particle size 10-200 µm, pore diameter 20 nm, porosity 90-00%) in 40 g of NMP (N-methylpyrrolidine) at 70°C for 24 hours. The polymer solution was evenly coated onto a glass substrate using a doctor blade to a thickness of 100 µm. The substrate coated with the polymer solution was immersed in a container of distilled water as a non-solvent for 24 hours to induce a phase transition, then soaked in distilled water for 1 day to remove residual solvent, and then dried in an oven at 100°C for 1 day to prepare a porous polymer composite material (PEI / SI 10) with an additional pore structure.

[0074] Example 2

[0075] A porous polymer composite material (PEI / SI 30) was prepared in the same manner as in Example 1 above, except that 7g of polyetherimide pellets and 3g of silica aerogel were used.

[0077] Example 3

[0078] A porous polymer composite material (PEI / SI 50) was prepared in the same manner as in Example 1 above, except that 5g of polyetherimide pellets and 5g of silica aerogel were used.

[0080] Comparative Example 1

[0081] A porous polyetherimide material (PEI) was prepared in the same manner as in Example 1 above, except that only 10g of polyetherimide pellets were used.

[0083] Test Example 1: Flexibility Verification Test

[0084] The film-shaped materials prepared in the above Comparative Example and Examples 1 to 3 were produced into a film with a thickness of 50 μm.

[0085] Flexibility was verified by physical bending, and the results are shown in FIGS. 1a to 1d. (Fig. 1a: Comparative Example, Fig. 1b: PEI / SI 10, Fig. 1c: PEI / SI 30, Fig. 1d: PEI / SI 50)

[0086] From the results of Figures 1a to 1d, it was confirmed that the flexibility and durability were excellent regardless of the amount of silica aerogel added.

[0088] Test Example 2: Pore Structure Observation Test

[0089] The results of observing the cross-sections of the porous polyetherimide prepared in the above comparative example and the composite material prepared in the above example using a scanning electron microscope (SEM) are shown in Figures 2a (comparative example) and 2b (example 3).

[0090] From the results of Figures 2a and 2b, it was confirmed that in the case of the composite material of porous polyetherimide and silica aerogel, the silica aerogel is well dispersed in the pores and on the surface of the polyetherimide.

[0092] Test Example 3: Thermogravimetric Analysis (TGA)

[0093] For each of the above comparative examples and examples 1 to 3, thermogravimetric analysis (TGA) was performed using a TA Q500 (TA Instrument) at a temperature range of 30-800℃ under a condition of 10℃ / min, and the results are shown in Fig. 3.

[0094] From the results of Figure 3, it was confirmed that in the case of the comparative example porous polyetherimide, the weight decreased rapidly in the range of 500 to 600°C, whereas in the case of the example, the slope of the weight decrease became gentler as the silica aerogel content increased. In other words, it was confirmed that in the case of the example, heat resistance improved as the silica aerogel content increased.

[0096] Test Example 4: Heat Release Rate (HRR) Analysis

[0097] Heat release rate (HRR) analysis was performed for each of the above comparative examples and examples 1 to 3. Specifically, the heat release rate (HRR) analysis was performed using a micro combustion calorimeter (MCC) manufactured by Fire Testing Technology (FFT, UK), and flame retardancy was evaluated by assessing the total heat release (THR) and maximum heat release rate (pHRR), and the results are shown in Figure 4.

[0098] From the results of Figure 4, it was confirmed that the heat release rate of the porous polyetherimide in the comparative example was significantly high in the range of 500 to 600°C, whereas in the example, the amount of heat released decreased significantly as the content of silica aerogel increased, and thus excellent flame retardancy was exhibited.

[0100] Test Example 5: Confirmation of Flame Retardant Properties

[0101] Each of the film-shaped specimens prepared in the above Comparative Example and Examples 1 to 3 was burned to confirm flame-retardant properties. The results of visually checking whether the specimens deformed are shown in FIGS. 5a to 5d (Fig. 5a: Comparative Example, Fig. 5b: PEI / SI 10, Fig. 5c: PEI / SI 30, Fig. 5d: PEI / SI 50), and the results of scanning electron microscope (SEM) examination of the cross-section of each specimen after flame treatment are shown in FIGS. 6a to 6d (Fig. 6a: Comparative Example, Fig. 6b: PEI / SI 10, Fig. 6c: PEI / SI 30, Fig. 6d: PEI / SI 50).

[0102] From the results of FIGS. 5a to 5d and FIGS. 6a to 6d, it was confirmed that in the case of the comparative example, the flame retardancy was significantly reduced and the specimen was greatly deformed, whereas in the case of the example, as the content of silica aerogel increased, the specimen was maintained without deformation and the flame retardancy was greatly increased.

[0104] Test Example 6: Thermal Conductivity Analysis

[0105] The thermal conductivity of each film-type specimen prepared in the above Comparative Example and Examples 1 to 3 was measured according to ASTM D7984, and the results are shown in Table 1 below.

[0106] PEI PEI / SI 10 PEI / SI 30 PEI / SI 50 Thermal conductivity (W / mK) 0.0537 0.0518 0.0472 0.0465

[0107] From the results of Table 1, it was confirmed that the thermal conductivity of the composite materials of Examples 1 to 3 is lower than that of the comparative example, and in particular, as the content of silica aerogel increases, the thermal conductivity decreases significantly, further improving the thermal insulation performance.

[0108] Test Example 7: Density Measurement

[0109] The apparent density of each film-shaped specimen prepared in the above Comparative Example and Examples 1 to 3 was calculated by measuring the weight and volume according to the ASTM D1622 method. Specifically, the length, width, and height of each of the five specimens prepared in the above Comparative Example and Examples 1 to 3 were measured, and the average density of the five specimens was calculated, and the results are shown in Table 2 below.

[0110] PEI PEI / SI 10 PEI / SI 30 PEI / SI 50 Average density (g / cm³) 3 ) 0.35 0.34 0.27 0.21

[0111] From the results in Table 2, the density of the film material manufactured by simply melting and processing commonly used polyetherimide is 1.27 g / cm³ 3 It is known that, however, in the case of the porous polyetherimide of the comparative example, a pore structure is introduced through a phase transition technique as in one embodiment of the present invention, thereby reducing the density, and in the case of Examples 1 to 3, it was confirmed that more effective weight reduction is possible as the silica aerogel content increases.

[0112] From the results of Test Examples 1 to 7 above, it was confirmed that the porous composite material according to one embodiment of the present invention exhibits excellent lightness, thermal insulation, and flame retardancy, and thus has excellent utility as a thermal insulation material.

Claims

Claim 1 A method for manufacturing a porous composite material comprising silica aerogel, comprising: a step of applying a polymer solution comprising silica aerogel and a polymer resin to a substrate; and a step of immersing the substrate coated with the polymer solution in a non-solvent solution to perform a phase inversion to form a porous composite material. Claim 2 A method according to claim 1, wherein the polymer resin is at least one selected from the group consisting of polyetherimide (PEI), polyimide (PI), polyamideimide (PAI), polystyrene (PS), polyetheretherketone (PEEK), polycarbonate (PC), polyethylene terephthalate (PET), polyethylene (PE), polypropylene (PP), acrylonitrile butadiene styrene (ABS), polybenzimidazole (PBI), and polyvinyl chloride (PVC), polysulfone (PSU), polyphenylene sulfide (PPS), polyurethane (PU), ethylene-vinyl acetate (EVA), polylactic acid (PLA), polyoxymethylene (POM), and polytetrafluoroethylene (PTFE). Claim 3 A method according to claim 1, wherein the polymer solution is obtained by dissolving and mixing the silica aerogel and the polymer resin in an organic solvent. Claim 4 A method according to claim 3, wherein the organic solvent is at least one selected from a polar aprotic solvent, a polar protic solvent, a nonpolar solvent, and a halogenated organic solvent. Claim 5 A method according to claim 3, wherein the organic solvent is at least one selected from the group consisting of N-methyl-2-pyrrolidone (NMP), dimethylacetamide (DMAc), dimethylformamide (DMF), methylene chloride (MC), and dimethyl sulfoxide (DMSO), tetrahydrofuran (THF), acetone, 1,4-dioxane, chloroform, ethylene glycol, propylene carbonate, trichloroethylene (TCE), and methyl ethyl ketone (MEK). Claim 6 A method according to claim 1, wherein the substrate is selected from a metal substrate, a glass substrate, a silicon substrate, and a plastic substrate. Claim 7 A method according to claim 1, wherein the polymer solution is applied to the substrate by any one method selected from doctor's knife, spin coating, dip coating, roll coating, screen coating, spray coating, flow coating, screen printing, ink jet, and drop casting. Claim 8 A method according to claim 1, wherein the nonsolvent is selected from the group consisting of water, C1-C6 lower alcohols, alkane solvents, and mixtures thereof. Claim 9 The method according to claim 1, wherein the average particle size of the silica aerogel is 0.1 to 1,000 μm. Claim 10 A method according to claim 1, further comprising, after the step of forming the porous composite material, the step of immersing the substrate on which the porous composite material is formed in distilled water to remove residual solvent and drying. Claim 11 A porous composite material manufactured by a method according to any one of claims 1 to 10. Claim 12 In paragraph 11, a porous composite material in the form of a film or foam. Claim 13 In claim 12, a porous composite material having a thickness of 1 μm to 30 cm of the film or foam. Claim 14 A porous composite material according to claim 11, which is used in a temperature range of -200℃ to 400℃. Claim 15 An insulating material comprising a porous composite material manufactured by a method according to any one of claims 1 to 10.